Teoria do prospecto e as diferenças de comportamento perante o risco entre gênero, escolaridade e idade - Falleiro, Marcos Paulo da Silva (2014)
This study investigates whether there are differences on risk behavior between men and women, between different levels of education and between ages. For this purpose, it makes use of Kahneman and Tversky (1979) and Tversky and Kahneman s (1992) prospect theory, which is part of the behavioral economics area, and estimates the parameters of the utility function and of the probability weighting function that denote how individuals give value (or utility) to concrete outcome and how they interpret probabilities. To obtain the certainty equivalents necessary to the estimation, an experiment was realized with students and professors of undergraduate and graduate courses at PUC-RS. This experiment consisted in a application of a dynamic questionnaire in which the participants should indicate their preferences between a bet and a sure gain. This process was repeated six times to each bet, making it possible to surround the equivalent certainties of each of the bets, without the need to ask directly its value to the participants. The questionnaire was developed in a spreadsheet software and consisted in 42 questions, being 6 bets crossed with 7 different probabilities (moreover, 3 questions were repeated to check for consistency). The methodology used in the experiment is partly new and partly extracted from Gonzalez and Wu (1999). The results are not definitive, but point in the direction on the existence of important differences of risk behavior between the researched groups. Accordingly, some hypotheses can be considered that explain the results: women would be more risk averse than men because they weight probabilities less linearly; a higher education would indicate a better understanding of probabilities, that takes to a decreasing in risk seeking; and last, a higher age would cause an increasing in risk aversion because it decreases the attractiveness of the monetary outcomes involved.